STUDI ATAS FATWA DSN-MUI TERHADAP AKAD-AKAD DALAM LETTER OF CREDIT (L/C) IMPOR DAN EKSPOR SYARIAH - Khoiruddin, Khoiruddin (ASAS, 2011)
Abstak: The existence of letter of credit which is really accordance with Islamic syariah principles has been waited by moslem bussinessmen who want to run their religion values in all their life. The conventional L/C has been existed is considered as on syariah L/C due to its practice still applicates the interest system.The regulation of L/C Syariah has been existed in Act No. 21/2008 concerning Perbankan Syariah, in article 19 p, and long before the act was born, the existence of L/C Syariah has been mentioned in Fatwa Dewan Syariah Nasional MUI NO.34/DSN-MUI/IX/2002 concerning L/C Impor Syariah and Fatwa Dewan Syariah Nasional MUI No. 35/DSN-MUI/IX/2002 concerning L/C Ekspor Syariah. L/C Syariah can applicate some models of akads/contracts, such as : wakalah bil ujrah, qardh, murabahah, salam/istisna’, mudarabah, musyarakah, hawalah and al-bai’. From the variety of contract models which can be applicated to the L/C Syariah, wakalah bil ujrah and Murabahah are considered as the most efficient, safest, and the most minimum risky. Wakalah bil ujrah and Murabahah are also an aggreement that closest to the goal of L/C existence, that is: makes the international trade process become easier. Keywords: Fatwa DSN-MUI, L/C Syariah.